PECULIARITIES OF PROCESSES OF THE HULL CASTINGS PRODUCTION OF HIGH-STRENGTH CAST IRONS - M. I. Karpenko; M. A. Sajkov; M. V. Mamaeva; D. M. Kukij; V. F. Odinochko; A. P. Melnikov (Литьë и металлургия)
Investigations and production tests of a number of important basic castings of high-duty cast iron with ball-like and vermicular shape of graphite are carried out.